Konsep Jarak Terdekat dalam Menghadap Kiblat - Siti Tatmainul Qulub (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
Facing the Qibla is a legitimate requirement in the salat. In some recent astronomical literature mentioned that the meaning of the direction of Qibla is the closest distance to the Kaaba. In the literature books of fiqh as well as classical celestial sphere is not mentioned meaning Qibla direction as the closest distance to the Kaaba (Mecca). Qiblah word in the verse means "shatrah" and "jihah" where both have a sense of direction facing, without indicating whether the direction of the nearest or farthest. This paper explore the concept of the meaning of the closest distance in defining the direction facing the Qiblah. Meaning the search starts from facing the Qibla direction by fuqoha 'followed by the meaning of facing the Qibla direction by the astronomer or an astronomer at the time of the Prophet until today. In that search will be sought from since when appearing purport Qibla direction as the closest distance and who within the scientific community.